2019
DOI: 10.1016/j.midw.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The mental health and wellbeing of midwifery students: An integrative review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Our findings suggest that formal opportunities for peer support may also enhance midwifery students' mental wellbeing and ability to cope with the emotional demands of midwifery practice. The recent integrative review (Oates et al, 2019) on midwifery student wellbeing identified three studies which evaluated interventions to address midwifery student wellbeing. Of these, two studies fo-cused on helping students improve their coping skills through workshop attendance (Cummins et al, 2018;Sahebalzamani et al, 2014), but one study (Bass et al, 2016) described the positive effect of 'student support circles' on students' sense of belonging and connectedness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that formal opportunities for peer support may also enhance midwifery students' mental wellbeing and ability to cope with the emotional demands of midwifery practice. The recent integrative review (Oates et al, 2019) on midwifery student wellbeing identified three studies which evaluated interventions to address midwifery student wellbeing. Of these, two studies fo-cused on helping students improve their coping skills through workshop attendance (Cummins et al, 2018;Sahebalzamani et al, 2014), but one study (Bass et al, 2016) described the positive effect of 'student support circles' on students' sense of belonging and connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…A recent integrative review of the research on the mental health and wellbeing of midwifery students (Oates et al, 2019) identified few studies focusing solely on the mental health and wellbeing of midwifery students. Mental health may be defined as the presence or absence of symptoms of mental illness, whereas mental wellbeing may be defined as a combination of experience of positive emotions, satisfaction with life and having the psycholog-ical resources to cope with adversity (Waldron, 2010).…”
Section: Main Body Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more studentcentered research is needed to identify stressors, barriers, and facilitators of educational stress [2]. There is not sufficient evidence to define the state of midwifery student mental health especially stressors in clinical education, when compared to other students or healthcare professionals [23]. There is a growing need for improving the clinical learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…There is not sufficient evidence to define the state of midwifery student mental health especially stressors in clinical education, when compared to other students or healthcare professionals [23].…”
mentioning
confidence: 99%